Microbial lectome versus host glycolipidome: How pathogens exploit glycosphingolipids to invade, dupe or kill - Bereznicka, Anna; Mikolajczyk, Krzysztof; Czerwinski, Marcin; Kaczmarek, Radoslaw (Frontiers in Microbiology, 2022)
Glycosphingolipids (GSLs) are ubiquitous components of the cell membranes, found across several kingdoms of life, from bacteria to mammals, including humans. GSLs are a subclass of major glycolipids occurring in animal lipid membranes in clusters named “lipid rafts”. The most crucial functions of GSLs include signal transduction and regulation as well as participation in cell proliferation. Despite the mainstream view that pathogens rely on protein-protein interactions to survive and thrive in their hosts, many also target the host lipids. In particular, multiple pathogens produce adhesion molecules or toxins that bind GSLs. Attachment of pathogens to cell surface receptors is the initial step in infections. Many mammalian pathogens have evolved to recognize GSL-derived receptors. Animal glycosphingolipidomes consist of multiple types of GSLs differing in terminal glycan and ceramide structures in a cell or tissue-specific manner. Interspecies differences in GSLs dictate host specificity as well as cell and tissue tropisms. Evolutionary pressure exerted by pathogens on their hosts drives changes in cell surface glycoconjugates, including GSLs, and has produced a vast number of molecules and interaction mechanisms. Despite that abundance, the role of GSLs as pathogen receptors has been largely overlooked or only cursorily discussed. In this review, we take a closer look at GSLs and their role in the recognition, cellular entry, and toxicity of multiple bacterial, viral and fungal pathogens.